Effect of Climate on Morphology and Development of Sorted Circles and Polygons - Tomáš Uxa; Peter Mida; Marek Křížek (Permafrost and Periglacial Processes)
Sorted circles and polygons are widespread features of periglacial landscapes, but the controls on their development remain poorly understood, impeding their use as palaeoenvironmental indicators. We investigate the relationship of sorted circles and polygons to altitude in the northern Billefjorden area, central Svalbard. The patterns occur in two distinct elevation zones, below 200–250 m asl and above 600 m asl. The higher‐elevated patterns have smaller diameters and shallower sorting depths due to a thinner active layer at higher elevations, suggesting that sorted patterns can indicate climate conditions and ground thermal state when the patterns initiated. Geology is believed to be of less importance for pattern morphology in the study area, causing only its fine‐scale variations. The pattern diameter‐to‐sorting depth ratios have a median value of 3.57, consistent with previous studies and theoretical models of patterned‐ground formation involving circulation mechanisms. Large‐scale sorted patterns may develop over centennial timescales in this high‐Arctic environment. They are probably not in equilibrium with present‐day climate conditions and have probably formed throughout the Holocene. Copyright © 2017 John Wiley & Sons, Ltd.